TABLE OF CONTENTS (JEAR VOL. 10, ISSUE, 2, JUNE 2025) - Admin, Jearcons (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Journal of Economics and Allied Research (JEAR) is a peer-reviewed open access journal published by the Centre for Contemporary Economics and Allied Research, Department of Economics, University of Nigeria, Nsukka in collaboration with K-injo Publishers Limited. The journal accepts state of the art research in the following areas: All areas of mainstream economics as well as other areas such as education, environment, health, economics geography, development issues, social and cultural issues, petroleum and energy economics, political economy, and public policy. The journal publishes articles quarterly (March, June, September and December Issues). The journal can also publish more than four times a year depending on the rate of submission and also based on editorial board’s decision. Articles involving cross sectional, cross country, time series and panel studies are welcome. In selecting articles for publication (from articles that have passed the review process) the journal will endeavour to strike a balance among the subject areas and methodological approaches. In order to facilitate the speed of acceptance, articles addressing current economic problems or challenges with specific policy relevance will be given priority.